Ki Hadjar Dewantara's View on Freedom to Learn in His Relationship with Character Improvement - Teti Wahyuni; Jarjani Usman; Sri Suyanta (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The development of an intellectually curious and morally upright next generation is one of Indonesia's stated educational objectives. The principle of